2018
DOI: 10.1186/s12863-018-0665-0
|View full text |Cite
|
Sign up to set email alerts
|

Putative candidate genes responsible for leaf rolling in rye (Secale cereale L.)

Abstract: BackgroundRolling of leaves (RL) is a phenomenon commonly found in grasses. Morphology of the leaf is an important agronomic trait in field crops especially in rice; therefore, majority of the rice breeders are interested in RL. There are only few studies with respect to RL of wheat and barley; however, the information regarding the genetic base of RL with respect to the shape of leaf in rye is lacking. To the best of our knowledge, this is the first study on the localization of loci controlling RL on high den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 32 publications
(55 reference statements)
0
11
0
Order By: Relevance
“…Five of these QTLs significantly co-localized with QTLs associated with plant productivity. In rye (RR, 2n = 14), a distant relative of wheat, four stable QTLs for flag leaf rolling located on chromosomes 3R, 5R, and 7R were reported 25 . However, only few studies on leaf rolling is reported in hexaploid wheat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five of these QTLs significantly co-localized with QTLs associated with plant productivity. In rye (RR, 2n = 14), a distant relative of wheat, four stable QTLs for flag leaf rolling located on chromosomes 3R, 5R, and 7R were reported 25 . However, only few studies on leaf rolling is reported in hexaploid wheat.…”
Section: Discussionmentioning
confidence: 99%
“…dicoccoides ) identified 11 significant QTLs associated with flag leaf rolling 24 . In another related species Secale cereale (Rye), four stable QTLs associated with leaf rolling were reported on chromosomes 3R, 5R, and 7R 25 utilizing DArT markers. Wheat is a polyploid species and identifying genes with minor effects like those affecting drought tolerance is a daunting task.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, rye has been reported to be more resistant to biotic (Arseniuk, Foremska, Góral, & Chełkowski, ; Gaikpa, Lieberherr, Maurer, Longin, & Miedaner, ; Miedaner, Reinbrecht, Lauber, Schollenberger, & Geiger, ) and abiotic (Bartoš et al, ; Myşków, Góralska, Lenarczyk, Czyczyło‐Mysza, & Stojałowski, ; Villareal, Bañuelos, Mujeeb‐Kazi, & Rajaram, ) stress factors compared to wheat and triticale. However, rye can be infected with several diseases including Fusarium head blight (FHB), reducing grain size and grain yield and contaminating the grains with mycotoxins, like deoxynivalenol (DON) and zearalenone (ZON) (Miedaner & Geiger, ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies involving the QTL mapping of other minor and pseudo-cereals, however, are relatively limited and mostly include studies in rye (Erath et al 2016, Miedaner et al 2018, Myśków et al 2018, Wang et al 2015, oat (Admassu-Yimer et al 2019, Babiker et al 2015, Pellizzaro et al 2016, Schneider et al 2015, Sunstrum et al 2018, Zimmer et al 2018, and millet. Of the various types of millet, pearl millet (Ambawat et al 2016, Aparna et al 2015, Kumar et al 2016b, 2018, Pucher et al 2018, Punnuri et al 2016, Taunk et al 2018 and foxtail millet (Fang et al 2016, Mauro-Herrera and Doust 2016, Ni et al 2017, Odonkor et al 2018, Wang et al 2017a, 2017b have received the majority of research attention, although one study also focused on proso millet (Rajput et al 2016).…”
Section: Biparental Qtl Mappingmentioning
confidence: 99%